Association between social phobia and allergic asthma in adolescents - Han, Shuang; Wang, Tao; Wang, Jiaojiao; Han, Zhihua; Wang, Pengfei (Frontiers in Allergy, 2025)
BackgroundSocial phobia and asthma pose threats to the health of adolescents at the psychological and physical levels, respectively. The aim of this study was to explore the association between social phobia and asthma in this population.MethodsA total of 337 adolescent asthma patients and 337 adolescent controls were included. Social phobia status was assessed using the Mini Social Phobia Inventory (Mini-SPIN) and the Social Anxiety Scale for Children (SASC). The ratio of forced expiratory volume in 1 s to forced vital capacity (FEV1/FVC), the percentage of forced expiratory volume in 1 s to its predicted value (FEV1%pred), peak expiratory flow, and peripheral levels of plasma eosinophil, immunoglobulin E (IgE), leukotriene, and histamine were also measured. Multivariate logistic or linear regression analyses were used to evaluate the associations between social phobia-related variables and asthma-related variables.ResultsElevated scores on the Mini-SPIN and SASC scales were associated with an increased risk of asthma in adolescents (both P < 0.001). This association remained consistent among adolescents with new-onset asthma (both P < 0.001) and those experiencing asthma recurrence in adolescence following a childhood asthma history (both P < 0.001). Meanwhile, higher scores on both scales correlated with decreased FEV1/FVC (both P < 0.001) and FEV1%pred (P = 0.001 and P = 0.002, respectively) and elevated leukotriene levels (P < 0.001 and P = 0.001, respectively). However, neither scale showed an association with plasma eosinophil, IgE, or histamine levels.ConclusionAmong adolescents, there was a significant association between social phobia and asthma.